2019
DOI: 10.1016/j.imr.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tai chi mind-body approach on the mechanisms of gulf war illness: an umbrella review

Abstract: Gulf War illness (GWI) is a chronic and multisymptom disorder affecting military veterans deployed to the 1991 Persian Gulf War. It is characterized by a range of acute and chronic symptoms, including but not limited to, fatigue, sleep disturbances, psychological problems, cognitive deficits, widespread pain, and respiratory and gastrointestinal difficulties. The prevalence of many of these chronic symptoms affecting Gulf War veterans occur at markedly elevated rates compared to nondeployed contemporary vetera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Some have evaluated multiple interventions for a single condition [ 8 16 ], whilst others have focused only on Tai Chi interventions for either a single condition [ 17 – 22 ] or multiple conditions [ 23 27 ]. Limitations of the overviews evaluating only Tai Chi interventions [ 17 – 27 ] were the potential for language bias [ 17 , 18 , 22 , 23 , 25 27 ], reporting bias in which the most favourable results were emphasized [ 23 , 27 ], and reporting multiple estimates of effects/results for the same or similar outcome and population, with limited or no discussion about conflicting results or overlapping of the primary studies [ 18 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some have evaluated multiple interventions for a single condition [ 8 16 ], whilst others have focused only on Tai Chi interventions for either a single condition [ 17 – 22 ] or multiple conditions [ 23 27 ]. Limitations of the overviews evaluating only Tai Chi interventions [ 17 – 27 ] were the potential for language bias [ 17 , 18 , 22 , 23 , 25 27 ], reporting bias in which the most favourable results were emphasized [ 23 , 27 ], and reporting multiple estimates of effects/results for the same or similar outcome and population, with limited or no discussion about conflicting results or overlapping of the primary studies [ 18 25 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large number of SRs, most of which were screened using a partially blinded process to help reduce the risk of selective reporting bias, it is possible that some populations and outcomes were also missed. However, we are con dent that we have reported the important outcomes also highlighted in other SRs of SRs [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Strengths and Limitations Of This Overviewmentioning
confidence: 89%
“…Given the large number of SRs of Tai Chi, SRs of SRs (henceforth referred to as overviews) are increasingly being conducted [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Some have evaluated multiple interventions for a single condition [18][19][20][21][22][23][24][25][26], whilst others have focused only on Tai Chi interventions for either a single condition [7][8][9][10][11][12] or multiple conditions [13][14][15][16][17]. Limitations of the overviews evaluating only Tai Chi interventions [7][8][9][10][11][12][13][14][15]...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tai Chi is a multi-component intervention that integrates physical, psychological, emotional, mental and behavioral elements, which can have an impact on the body and spirit of patients, resulting in bene cial health outcomes [18]. Research has shown that Tai Chi exercises can improve muscle strength, proprioceptive sensitivity and neuromuscular activity, as well as physical and mental integration to reduce pain, thereby improving physical, mental and psychosocial health and overall quality of life, ideal for symptomatic KOA [19].…”
Section: Background and Rationale {6a6b}mentioning
confidence: 99%